Managing Stakeholders : A Case study on Small Scale Industries - Tyagi, Ruchi (Journal of Commerce and Trade, 2008)
All businesses operate within a complex system of interests and influences, those people and groups that may affect the company and, in turn, be affected by the company’s actions and decisions are its stakeholders and managing the same is stakeholder management, further the stakeholder management is emerging as an important theme in small scale sector, which is a vital constituent of India’s industrial sector contributing significantly to the countries GDP and exports earnings besides providing the employment opportunities. It has been estimated that an investment of 1 million rupees in fixed assets in the SSI sector produces 4.62 million rupees worth of goods or services with tremendous value addition. The number of small-scale units has substantially increased from an estimated 0.87 million in 1980-81 to over 3 million in 2000.The direct exports from the SSI sector account for nearly 35% of the total exports. Besides direct exports, it is estimated that small-scale industrial units contribute around 15% to exports indirectly. The non-traditional products account for more than 95% of SSI exports. The product groups where the SSI sector dominates in exports are sports goods, readymade garments, woolen garments & knitwear, jewelry etc.